Uji Performa Sistem Hidrolik Alat Peraga Mini Excavator Zhugimada - Nur Esa, Suhada; Prihadianto, Braam Delfian; Anggoro Hasan, Dani; Ardean Kurnianto Prayitno, Yosephus; Septian, Miko; Nurul Hidayat, Anisa (P3M Politeknik Negeri Cilacap, 2025)
Practical learning activities on heavy equipment units are important because they increase understanding of work systems and provide an actual picture. The need for excavators for practicum activities in vocational education is currently hampered by price issues when commercial units are used as learning tools, therefore learning media in a more concise form are needed without ignoring important aspects. The manufacture of mini excavator props has been carried out but research related to work system testing is still rare, so performance testing of the work system is needed to ensure the performance of the props. The aim of this research is to test cylinder speed, cylinder pressure and cylinder drift using quantitative observation methods with variations in zero capacity, struck capacity and heaped capacity transport. From the test results, it was found that the cylinder speed values ​​were between 0.028–0.081 m/sec, the cylinder pressure was 17–20 bar for the boom, 65–72 bar for the arm, 24–34 bar for the bucket and the increase in length in the cylinder drift test was 0 mm